Analyzing Integrated Curriculum Grade (1-3): Concepts, Development and Practices in Nepal - Kunwar, Rajendra; Acharya, Nara Hari (Teacher Half-Yearly Journal, 2025)
This article explores the concept, development, and implementation of the integrated curriculum for Grades 1-3 in Nepal. The integrated curriculum is a powerful tool for providing a well-rounded education beyond subject-specific knowledge and skills, fostering critical thinking and interdisciplinary connections. The article examines the overall curriculum development process, comparing it with the Beane (1997) curriculum framework. It assesses the alignment between the Nepalese curriculum and the Beane framework by conducting a descriptive analysis based on reviewing and comparing various documents. The findings demonstrate that Nepal's concept and curriculum development process align closely with the Beane (1997) integrated curriculum framework. However, challenges arise in effectively implementing the curriculum due to factors such as inadequate teacher preparedness, limited resources, assessment difficulties, and insufficient community involvement. To address these challenges and fully operationalize the integrated curriculum, the article emphasizes the importance of collaborative efforts from policymakers, educational authorities, teachers, parents, and the wider community. Recommendations are provided to the relevant authorities, highlighting the need to prioritize teacher professional development and foster stakeholders' active participation to ensure the effective implementation of the integrated curriculum in line with its intended goals.